2015
DOI: 10.1093/pubmed/fdv006
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy in a population-based sample of adult men and women in a South Eastern European country

Abstract: Sociodemographic correlates of HL among Albanian adults showed similar trends with those observed in other former communist countries of Europe. Current findings may help policymakers tailor accordingly future interventions and programs to improve health status of Albanian citizens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 23 publications
5
42
0
Order By: Relevance
“…General health literacy scores (mean = 35.5) are consistent across eight European countries, including across their subpopulations aged 25 years and younger (mean health literacy score = 35.10). Health literacy among the young adults in our study was most similar to that in Ireland [ 5 ]; lower than in Netherlands, Poland [ 5 ], and Albania [ 29 ]; and higher than in Germany, Austria, Bulgaria [ 5 ], and Japan [ 8 ].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…General health literacy scores (mean = 35.5) are consistent across eight European countries, including across their subpopulations aged 25 years and younger (mean health literacy score = 35.10). Health literacy among the young adults in our study was most similar to that in Ireland [ 5 ]; lower than in Netherlands, Poland [ 5 ], and Albania [ 29 ]; and higher than in Germany, Austria, Bulgaria [ 5 ], and Japan [ 8 ].…”
Section: Discussionmentioning
confidence: 48%
“…The European Health Literacy Survey Questionnaire (HLS-EU-Q), recently developed by the European Health Literacy Survey Consortium (HLS-EU) [ 1 , 5 ], is based on an integrated health literacy model of competencies in the processes of accessing, understanding, appraising, and applying health-related information within three domains: healthcare, disease prevention, and health promotion [ 2 ]. The questionnaire approaches health literacy as a multidimensional construct and has been adapted for use in different European [ 1 , 5 , 6 , 28 , 29 ] and non-European [ 7 , 8 ] countries. Although there have been attempts to develop health literacy assessment tools for young adults specifically, they remain in the pilot stage [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an HLHO is designed to help build a person-centered, evidence-based, and quality-driven healthcare system [20]. Despite this, current healthcare systems are nowadays designed on the assumption that their users have adequate HL levels [21].…”
Section: Communicates Clearly What Health Plans Cover and What Indivimentioning
confidence: 99%
“…The available evidence from population studies shows that health literacy may depend on sex, age, level of education, economic and/or social status, and the type of vocational activities. In the research carried out to date, it has been demonstrated that lower HL is displayed by men rather than by women [4][5][6][7], by people having lower levels of educational attainment than by those with higher levels [4][5][6][7][8][9][10][11][12], by single people than by married people [7,13], by people with lower social status than by those with a higher status [8,11,14], by people of lower rather than those of higher economic status or income [4,[7][8][9]13,15,16] and, finally, by people living in more challenging conditions [6,8]. In most studies, there was also a general trend for HL decreasing with age [4,6,8,9,15].The efforts undertaken in the last decade resulted in a comprehensive assessment of the consequences of limited health literacy.…”
mentioning
confidence: 99%